2012
DOI: 10.1097/ico.0b013e318219aa7a
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Collagen Cross-Linking Before Ferrara Intrastromal Corneal Ring Implantation for the Treatment of Progressive Keratoconus

Abstract: FR implantation after CXL is a safe and efficacious treatment option for managing selected patients with progressive keratoconus. Good results in terms of visual acuity, postoperative residual refractive error, and keratometry values were obtained. Longer follow-up would be valuable to confirm the stability of these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 18 publications
0
31
1
Order By: Relevance
“…He had grater reduction in cylinder and keratometry than ICR alone, which testifies the effect of cross-linking. The study of Henriquez et al [17], who used cross-linking before ICR, had better results than our study. It demonstrates the additional effect of ICR, as following: UCVA preoperatively was 1.11 logMAR, after CXL 0.75 logMAR P = 0.03, and 0.23 logMAR after 6 months after ICR implantation P < 0.001; BCVA at 1 year was 0.05; spherical equivalent had a P value < 0.001; keratometric values at 6 months after ICR implantation were statistically decreased P = 0.01.…”
Section: Discussioncontrasting
confidence: 51%
“…He had grater reduction in cylinder and keratometry than ICR alone, which testifies the effect of cross-linking. The study of Henriquez et al [17], who used cross-linking before ICR, had better results than our study. It demonstrates the additional effect of ICR, as following: UCVA preoperatively was 1.11 logMAR, after CXL 0.75 logMAR P = 0.03, and 0.23 logMAR after 6 months after ICR implantation P < 0.001; BCVA at 1 year was 0.05; spherical equivalent had a P value < 0.001; keratometric values at 6 months after ICR implantation were statistically decreased P = 0.01.…”
Section: Discussioncontrasting
confidence: 51%
“…[24][25][26][27][28][29][30][31][32] In a retrospective nonrandomized comparative case series by Chan and Sharma, 25 12 eyes (9 patients) underwent inferior-segment Intacs placement without CXL and 13 eyes (12 patients) underwent inferior-segment Intacs placement followed by CXL with UV light and riboflavin. Previous studies reported that combining these two complementary interventions has been shown to be safe and effective.…”
Section: Combination Treatment Of Corneal Crosslinking and Intracornementioning
confidence: 99%
“…Various sequences of treatments have been described: performing CXL before ICRS implantation, 27,30,31 after, 24,[27][28][29]33,37 or on the same day 25,26,37 with controversial results. It is still unclear whether the cornea first needs to be reshaped by the ICRS before it is stabilized by CXL, whereas CXL before ICRS placement may stiffen the cornea and prevent the ICRS from causing significant corneal flattening.…”
Section: Combination Treatment Of Corneal Crosslinking and Intracornementioning
confidence: 99%
See 1 more Smart Citation
“…There are many combination procedures such as CXL and ICRS implantation [107][108][109][110] and CXL and PRK [111][112][113][114][115] reported in the literature. The purpose of these combined procedures is to augment the effect of the individual procedure in KC.…”
Section: Momentioning
confidence: 99%